Recognition and Parameter Extraction of One-Dimensional Electronic Scanning for 3D Radar. (24th December 2014) - Li, Cheng; Wang, Wei; Shi, Longfei; Wang, Xuesong
Abstract : Most of the existing antenna scan type (AST) identification techniques focus on only mechanical scanning (MS) and rarely research electronic scanning (ES), especially one-dimensional (1D) ES. This paper proposes a recognition and parameter extraction method of 1D ES for 3D radar, which employs both MS and ES. An ES pattern simulator is designed to synthesize pulse amplitude (PA) data first. Then 1D ES is distinguished from MS and two-dimensional (2D) ES based on the features extracted from the difference sequences of beam sequence, such as resemblance coefficient (RC) and variance. Subsequently, two vital parameters for 1D ES are extracted, namely, beam position number in elevation and pulse number in a beam position. Finally, some simulation results are shown to validate the proposed algorithm.